Unplanned Student Pregnancy: Should the University Be There for Its Students? - E. Yu. Samuticheva (Высшее образование в России)
The issue of discouraging students from having an induced termination of pregnancy is still relevant. Studying at university is a socialization stage, coming after finishing school or college. In this period students may not only choose their future profession, but also their partner. Their relationship with the opposite sex may result in the unplanned pregnancy that can affect the student’s plans. In this case, owing to various reasons, the student is likely to seek a termination of the pregnancy. However, this medical intervention could result in negative reproductive health outcomes. Moreover, until now it has been carrying moral stigma. The present paper aims to research students’ opinions concerning support measures, provided to students by their universities in case of the pregnancy during their study. The results of the survey through the Google Forms have revealed the students’ need for these measures. Thus, 91,2% of 650 respondents stated that the university support is vital for both the pregnant girl and the future father. On the basis of the received answers the author suggests changing the policy of the universities by increasing their role in discouraging students from the termination decision and provide recommendations for the creation of the anti-crisis team, offering the support to the students in difficult life situations including cases of the unplanned pregnancy. In addition, the author deriving the conclusions from polling the students is the first to have suggested the various means of interaction between the university and other non-profit organizations that can provide assistance to pregnant women or mothers in need.